Effects of induced maternal hypothyroidism on the ovarian development of offspring rats - Radovanović Anita; Roksandić D.; Šimić Marija; Marković Danica; Gledić D. (Acta Veterinaria, 2012)
The effects of propylthyouracil (PTU) induced hypothyroidism of rats during pregnancy and lactation on offspring ovarian development and maturation were studied. Thyroid hormones and thyroid stimulating hormone (TSH) concentrations were determined using the radioimmunoassay method in order to verify the hypothyroid status of treated mothers and their two months old pups. The ovaries of the offspring were processed for light microscopy analysis on the day of the first estrus after the 60th day of age. Histological analysis including follicle count was performed on serial sections stained with haematoxyline/eosin and on semithin sections stained with methylene blue. A significant increase of serum TSH and decrease in T3 and T4 levels was observed in treated mothers compared to controls. The levels of measured hormones in the control and PTU-treated two months old rats were not significantly different. Ten percent of 60-dayold treated females did not reach estrus and they were sacrificed in diestrus. The secondary interstitial cells were the dominant structures in the ovaries. The number of healthy growing and early antral follicles was markedly decreased. Ovaries of treated rats contained relatively few antral follicles, significantly more atretic antral follicles and a decreased number of corpora lutea, compared to controls. These results indicate that lack of thyroid hormones during prenatal and early postnatal development impair ovarian development in rats. [Projekat Ministarstva nauke Republike Srbije, br. 175061]